Decomposition and nutrient release from shoot of legumes cover crops - Rosendo dos Santos, Valdevan; Correia Costa, Leonardo; Silveira Rabêlo, Flávio Henrique; Chisté, Loren; Macêdo Medeiros, Beatriz; dos Santos Dias, Carlos Tadeu (Comunicata Scientiae, 2025)
The cover crops can reduce soil exposure and erosion while enhancing nutrient cycling for crops. Effective implementation requires understanding how cover crops decompose and release nutrients to align with crop demand. This research assessed the decomposition rates and nutrient release of various legume residues commonly used as green manure or cover crops in agricultural systems. The study took place in a nutrient-deficient Red-Yellow Ultisol, using a split-plot design with different legume cover crop species: Crotalaria juncea, Crotalaria spectabilis, Cajanus cajan, Cajanus cajan (L.) Millsp), Dolichos lablab, Canavalia ensiformis and Mucuna aterrima as the main plots and six evaluation periods: 0, 30, 60, 90, 120, and 150 days after incorporation (DAI) as the subplots. Initial mass losses were observed in the first 60 days, followed by a slower decline over the study period. The order of nutrient accumulation in biomass was found to be: K > N > P > Ca > Mg. The Dolichos lablab species had the slowest decomposition rate, with a half-life of 43 days, while Cajanus cajan had the fastest, with a half-life of 65 days. Potassium reached its maximum by 30 DAI, indicating a rapid transfer to the soil. Nitrogen, P, and K contents decreased during different vegetative phases, highlighting the importance of proper timing for legume management. Hemp, Crotalaria spectabilis, Dolichos lablab, and Canavalia ensiformis were suitable for short-cycle vegetables due to rapid nutrient availability. Conversely, Cajanus spp., and Mucuna aterrima were better for extended soil coverage and slow nutrient release.